Silent Suffering: A Phenomenological Study of the Life Experiences of Students Victims of Culture-Based Bullying in a Multicultural Elementary School in Jambi City - Ferdiansyah, Muhammad; Susanti, Desy; Elfira, Ninil; Yulianti, Yulianti (Ghaidan: Jurnal Bimbingan Konseling Islam dan Kemasyarakatan, 2026)
Culture-based bullying in the context of multicultural elementary schools is a phenomenon that involves psychosocial factors that not only influence students' social interactions but also shape their self-identity and emotional well-being. Most previous studies focus on prevalence and risk factors quantitatively, thereby not delving into victims' subjective experiences, especially regarding the phenomenon of silent suffering. This study aims to explore and interpret the meaning of experience. subjective elementary school students who are victims of culture-based bullying, as well as construct a conceptual understanding of silent suffering. The research uses an interpretive phenomenological approach, involving students in Jambi City who have direct experience as victims. Data was collected through in-depth interviews and analyzed using Interpretative Phenomenological Analysis (IPA). The results of the study show that bullying is interpreted as an experience of rejection of one's own identity, which brings up hidden emotional wounds in the form of sadness, fear, social alienation, andhelplessness. Silence serves as a protective coping mechanism, but it also strengthens emotional isolation. This study concludes that silent suffering is the construction of the victim's main psychological experiences. The implication is that guidance and counseling services Needneed to develop an empathetic approach grounded in the subjective meaning of experiences to help restore students' psychological well-being.